Forvaltning av dyrevelferd i Norge Hvordan få lovverk til å virke? - Gezelius, Stig S.; Veggeland, Frode (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2022)
Animal Welfare Management in Norway is about how authorities can best promote high standards of well-being and respect for animals. In Norway, the Norwegian Food Safety Authority has primary responsibility for ensuring that businesses and persons comply with animal welfare laws and regulations. This book presents the results of a unique research project on the effects of the Food Safety Authority's efforts within land-based food industries, in which key questions were: What kinds of regulatory measures and oversight are most effective? Is organizing all regulatory activity under one authority worthwhile? Is industry receptive to oversight? How can the authority utilize measures such as guidelines, warnings or punishment to best effect? This book provides new insight into challenges associated with animal welfare management, an area that has previously been under-researched in Norway. The book is geared toward persons with supervisory roles as well as those working in industries that handle animals, but it will also be of interest to anyone concerned with animal welfare or oversight in general. The book can also be relevant for instruction at the higher educational level. The contributors have backgrounds in political science, law, sociology, social anthropology, veterinary and other livestock-related fields, as well as inspection services. The book has been edited by Stig S. Gezelius, a professor at the University of South-Eastern Norway, and Frode Veggeland, a professor at the University of Oslo and senior researcher at the Norwegian Institute of Bioeconomy Research (NIBIO). The editors are experienced in research into public administration and implementation of legislation.